Consultancy's consequences? a critical assessment of consultancy’s impact on management - Sturdy, Andrew (Henry Stewart Talks, 2015)
Grand claims of management consultancy, Impacts of management consultancy (projects and beyond), Reasons to be cautious: partial geographical coverage, Reasons to be cautious: cause and effect, Reasons to be cautious: conflicting evaluations, Reasons to be cautious: scapegoating, Reasons to be cautious: moving boundaries